The impact of aircraft noise on communities in the vicinity of the Ninoy Aquino International Airport - Abaya, Ernesto B. (Philippine Engineering Journal)
This paper investigates the effects of noise emitted by operating aircrafts using runway 06/24 of the Ninoy Aquino International Airport (NAIA) on communities, namely, Barangay San Dionisio and Barangay Rizal, which lie under the flight paths of the aircrafts. It presents the perceptions of respondents from the two communities mentioned on how they are affected by aircraft noise. A profile of the respondents' years of residence, occupation, sex, age and household income vis-a-vis with their perceptions on the effects of aircraft noise was also presented. Analysis showed that individuals experienced the effects of noise in varying degrees but there is a general tendency to foreground their view that they have "gotten used" to aircraft noise. Moreover, noise contours in the vicinity of the airport were plotted using Integrated Noise Model along with data on aircraft operations such as frequency of flights of different types of aircrafts, flight paths and weather conditions at NAIA.